2022
DOI: 10.1021/acs.joc.1c02561
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Furo[2,3-e][1,4]diazepin-3-one Derivatives through Tandem Cyclization/[4 + 3] Annulation Reactions

Abstract: A variety of furo­[2,3-e]­[1,4]­diazepin-3-one derivatives were facilely synthesized through one-pot tandem cyclization/[4 + 3] annulation reactions between enynamides and α-bromohydroxamates. The reactions proceeded efficiently at room temperature, and various functional groups were well tolerated. The obtained furo­[2,3-e]­[1,4]­diazepin-3­(2H)-ones containing a 7-membered dinitrogen-fused ring might be of biological and medicinal value. The products could be further derived using convenient procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…First, the non-linear effect experiments indicated that the active catalytic species in the key cycloaddition step might be formed by coordination of two ligands with palladium(0), 15 and the apparently beneficial influence of phosphoric acid A2 on the enantioselectivity was noted (Scheme 4a), 13 which was further verified by using the corresponding sodium salt of A2 (Scheme 4b). Based on the above experiments and previous reports, 5,11 a plausible catalytic mechanism was proposed. As illustrated in Scheme 4c, coordination of the π-acid catalyst Au( i ) with enynamide 1a promoted intramolecular 5- endo-dig cyclisation to generate dihydrofuran-fused azadiene I after subsequent isomerisation and protonolysis.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…First, the non-linear effect experiments indicated that the active catalytic species in the key cycloaddition step might be formed by coordination of two ligands with palladium(0), 15 and the apparently beneficial influence of phosphoric acid A2 on the enantioselectivity was noted (Scheme 4a), 13 which was further verified by using the corresponding sodium salt of A2 (Scheme 4b). Based on the above experiments and previous reports, 5,11 a plausible catalytic mechanism was proposed. As illustrated in Scheme 4c, coordination of the π-acid catalyst Au( i ) with enynamide 1a promoted intramolecular 5- endo-dig cyclisation to generate dihydrofuran-fused azadiene I after subsequent isomerisation and protonolysis.…”
Section: Resultsmentioning
confidence: 59%
“…Enynamides 1 , a class of readily accessible substrates, are liable to undergo 5- endo-dig cyclization in the presence of a π-Lewis acid catalyst, such as Au( i ) 5 and Ag( i ). 6 The resultant dihydrofuran-derived azadiene species I could serve as highly reactive 4π-components to assemble with various catalytically generated dipole-type intermediates, including N-heterocyclic carbene (NHC)-tethered enolates and homo-enolates, 7 enamines derived from aldehydes, 8 and π-allylpalladium-containing dipolar species, 9 furnishing various fused heterocycles enantioselectively (Scheme 1a).…”
Section: Introductionmentioning
confidence: 99%
“…However, some very recent investigations have shown that N ‐alkoxyhaloamides 1 (R 1 =OR) can also be useful players in these reactions (Scheme 1, eq. 2) [4] . For example, the efficient access to 1,2,4,5‐tetrahydro‐1,4‐benzodiazepin‐3‐ones 4 has been reported by Jin, Zhang and co‐workers by reaction with N ‐(2‐chloromethyl)aryl amides [5] .…”
Section: Introductionmentioning
confidence: 97%
“…10 Very recently, Zhou and co-workers reported the synthesis of furo [2,3-e][1,4]diazepin-3-one derivatives through tandem cyclization/[4 + 3] annulation reactions of enynamide with α-bromohydroxamates. 11 Zhou et al disclosed a catalyst-controlled cycloisomerization/[4 + 3] cycloaddition sequence to construct 2,3-furan fused dihydroazepines and 2,3-pyrrole-fused dihydrooxepines. 12 Besides, the Deng group achieved a gold/palladium bimetallic relay catalytic strategy for efficiently synthesizing furan-fused azepines via the cascade reaction with trimethylenemethanes (TMM).…”
Section: ■ Introductionmentioning
confidence: 99%
“…In 2020, Zhao et al elegantly demonstrated a highly stereoselective access to polyfunctionalized furan-fused nine-membered heterocycles by sequential Au­(I) and Pd catalytic cycloisomerization/[4 + 5] annulation with vinyl ethylene carbonates (VECs) . Very recently, Zhou and co-workers reported the synthesis of furo­[2,3- e ]­[1,4]­diazepin-3-one derivatives through tandem cyclization/[4 + 3] annulation reactions of enynamide with α-bromohydroxamates . Zhou et al disclosed a catalyst-controlled cycloisomerization/[4 + 3] cycloaddition sequence to construct 2,3-furan fused dihydroazepines and 2,3-pyrrole-fused dihydrooxepines .…”
Section: Introductionmentioning
confidence: 99%